Shaping the Flow: Ethnographic Analysis of a Manchester Parade Event. Issue 4 (7th August 2016) - Symons, Jessica
ABSTRACT: The Manchester parade is a celebration of 'all things Manchester'. Explicit attempts to nurture and encourage a creative outpouring from community groups are made by event organisers and artists. I found that the parade took its shape from different responses to the flow of activity. The emergent 'freezing' shape of the parade then influenced its further development. Drawing on notions of flow and freezing, I show how Ingold's emphasis on emergence can work together with Gell's emphasis on the web of social relations, and it is the two working in tandem that give an entity its shape. This analysis of activities at a local level provides an insight into how global forces impact on groups and individuals unprepared or unable to go with the flow.